Establishment of the first World Health Organization International Genetic Reference Panel for quantitation of BCR-ABL mRNA - White, Helen E.; Matejtschuk, Paul; Rigsby, Peter; Gabert, Jean; Lin, Feng; Lynn Wang, Y.; Branford, Susan; Müller, Martin C.; Beaufils, Nathalie; Beillard, Emmanuel; Colomer, Dolors; Dvorakova, Dana; et al. (Blood, 2010)
Serial quantitation of BCR-ABL mRNA levels is an important indicator of therapeutic response for patients with chronic myelogenous leukemia and Philadelphia chromosome–positive acute lymphoblastic leukemia, but there is substantial variation in the real-time quantitative polymerase chain reaction methodologies used by different testing laboratories. To help improve the comparability of results between centers we sought to develop accredited reference reagents that are directly linked to the BCR-ABL international scale. After assessment of candidate cell lines, a reference material panel comprising 4 different dilution levels of freeze-dried preparations of K562 cells diluted in HL60 cells was prepared. After performance evaluation, the materials were assigned fixed percent BCR-ABL/control gene values according to the International Scale. A recommendation that the 4 materials be established as the first World Health Organization International Genetic Reference Panel for quantitation of BCR-ABL translocation by real-time quantitative polymerase chain reaction was approved by the Expert Committee on Biological Standardization of the World Health Organization in November 2009. We consider that the development of these reagents is a significant milestone in the standardization of this clinically important test, but because they are a limited resource we suggest that their availability is restricted to manufacturers of secondary reference materials.